Manufacturing of W/steel composites using electro-discharge sintering process. (March 2022) - Ganesh, Vishnu; Leich, Lennart; Dorow-Gerspach, Daniel; Heuer, Simon; Coenen, Jan Willem; Wirtz, Marius; Pintsuk, Gerald; Gormann, Friedel; Lied, Philipp; Baumgärtner, Siegfried; Theisen, Werner; Linsmeier, Christian
Highlights: A novel ultra-fast sintering of W/steel-MMCs. Optimization of sintering pressure and discharge energy. CTE and specific heat capacity of composites in agreement with theoretical values. Thermal conductivity and elastic modulus lower than expected. Abstract: Tungsten-steel metal matrix composites are consolidated using electro-discharge sintering. At first steel and tungsten powders are sintered separately and then 25 vol% W, 50 vol% W and 75 vol% W mixed powders are sintered. A thorough process parametric study is carried out involving analysis of the influence of particle size distribution, sintering pressure, and discharge energy on the maximum discharge current and obtained residual porosity. Thermal expansion coefficient and the specific heat capacity of the optimized sintered composites are almost same as their theoretical values, however the thermal conductivities and the mechanical properties are lower than the expected values.